Two-Dimensional Immobilized Metal Affinity Electrophoresis for Capturing a Phosphoprotein - Gupta, Shalini (Association of Biomolecular Resource Facilities, 2010)
A two-dimensional immobilized metal affinity electrophoresis method is described here. In this method, ferric ions are immobilized in the second-dimensional polyacrylamide gel to extract the phosphoprotein β-casein from a mixture containing proteins with a broad range of pI and MW. Native 7.5–15% gradient tris-glycine gel with SDS tris-glycine gel running buffer are used so that proteins can be separated according to their molecular mass in the second dimension.